2013
DOI: 10.5489/cuaj.727
|View full text |Cite
|
Sign up to set email alerts
|

The association between tumour density and prostate cancer recurrence following radical prostatectomy

Abstract: Purpose: Tumour density (TD) may be an independent prognostic factor in men with prostate cancer. The purpose of this study was to evaluate the association between prostate cancer TD and recurrence following radical prostatectomy. Materials and Methods: Between 1995 and 2007, 645 patients from The Ottawa Hospital or Memorial Sloan-Kettering Cancer Center who had cancer and prostate volumes measured from radical prostatectomy specimens. Tumour density was defined as the relative tumour to prostate volume (tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…As part of the in vivo phase of their investigation, they also showed that suppression of CENPF resulted in reduced mpMRI visibility of tumors and decreased cell growth rate, lowering cell density of tumors, decreasing the vascular marker CD31 and proliferation marker Ki67 33 . This increase in proliferative signaling in mpMRI‐visible cancer potentially explains previous observational reports that showed increased tumor size, cellular density, and microvasculature in conspicuous disease 27–29 …”
Section: Supportive Evidencementioning
confidence: 76%
See 1 more Smart Citation
“…As part of the in vivo phase of their investigation, they also showed that suppression of CENPF resulted in reduced mpMRI visibility of tumors and decreased cell growth rate, lowering cell density of tumors, decreasing the vascular marker CD31 and proliferation marker Ki67 33 . This increase in proliferative signaling in mpMRI‐visible cancer potentially explains previous observational reports that showed increased tumor size, cellular density, and microvasculature in conspicuous disease 27–29 …”
Section: Supportive Evidencementioning
confidence: 76%
“…These histopathological properties are informative, as Gleason grade, tumor volume, tumor cellular density, microvessel density, presence of cribriform and intraductal carcinoma, and tumors arising in the peripheral zone are all features associated with increased likelihood of disease recurrence following surgery 26–31 . As such, these pathological observations further suggest that tumor mpMRI visibility may have genuine prognostic utility.…”
Section: Supportive Evidencementioning
confidence: 96%
“…In another recent report using 645 samples, the percentage of gland involvement (referred to as tumor density) was an independent predictor of cancer recurrence, while tumor volume was not. As a limitation, the prostate tumors were quantified by one of two different methods, including a method that used constructed tumor maps and a method using tumor dimensions with a correction factor derived from the equation for an ellipsoidal structure [17].…”
Section: Discussionmentioning
confidence: 99%
“…Large tumors may display indolent behaviors, remaining confined in a large prostate with concomitant nodular hyperplasia. Several studies have shown that the percentage of the gland involved by the carcinoma has prognostic value [4,17,20,22], with this factor more predictive than the tumor volume [17,20]. Recently, several authors have suggested the use of the diameter of the largest tumor focus as a morphologic feature with prognostic value [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…The high incidence-to-mortality ratio predominantly reflects the favorable prognosis of localized disease, which is often curable with surgery/radiation. Recurrence occurs in 20%-30% of the patients [2]. For these cases, androgen deprivation therapy is most likely effective, but a large proportion eventually develops a hormone-independent disease that often progresses to castration-resistant prostate cancer (CRPC).…”
Section: Introductionmentioning
confidence: 99%